2009
DOI: 10.1007/s12257-009-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Importance of expression system in the production of unnatural recombinant proteins in Escherichia coli

Abstract: ^Äëíê~Åí= In this study, we investigated the efficiencies by which the pET and pQE expression systems produce unnatural recombinant proteins by residue-specific incorporation of unnatural amino acids, a method through which it was found that type of gene expression system tremendously influences the production yield of unnatural proteins in bëÅÜÉêáÅÜá~=Åçäá. Green fluorescent protein (GFP) and a single-chain Fv antibody against c-Met were utilized as model recombinant proteins while Lhomopropargylglycine (Hpg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The genes of n-GFP variants and s-GFP variants were respectively PCR amplified from pQE80-GFP [25] and pQE-80L-GFPhs1 [22] using the designed primers and cloned into Nde I and Xho I restriction sites of pET30b(+). The internal deletions were made using overlap extension PCR [26].…”
Section: Methodsmentioning
confidence: 99%
“…The genes of n-GFP variants and s-GFP variants were respectively PCR amplified from pQE80-GFP [25] and pQE-80L-GFPhs1 [22] using the designed primers and cloned into Nde I and Xho I restriction sites of pET30b(+). The internal deletions were made using overlap extension PCR [26].…”
Section: Methodsmentioning
confidence: 99%
“…used to amplify the gfp gene from GFP-mut3.1, which was previously cloned in the pET expression system [12]. The ompC promoter was then ligated with the gfp gene, after which the product was cloned into pUC19 to construct pOGFP1.…”
Section: Construction Of Plasmids Containing Aauz and Reporter Plasmidmentioning
confidence: 99%
“…Primers for the amplification of the dcuS, envZ, dcuB promoter, and ompC promoter genes were designed based on the reported E. coli genome sequence (Blattner et al, 1997) and primers for the amplification of the gfp gene (Miller et al, 2000) and the gfp mut3.1b gene (Ayyadurai et al, 2009) were designed based on the reported sequences. The genomic region containing 570 bp of the dcuB promoter gene was amplified from the chromosomal DNA of E. coli XL1-Blue with oligonucleotides DcuB F SalI and DcuB R BamHI ( Table 2).…”
Section: Construction Of the Plasmid For The Expression Of The Gfp Gementioning
confidence: 99%
“…This part of the promoter contains all three known binding sites for OmpR-P (Nara et al, 1986) and four of the nine LRP-binding sites present in the full-length chromosomal promoter (Ferrario et al, 1995). The gfp gene encoding GFP-mut3.1b was simultaneously amplified from the pET21a plasmid (Ayyadurai et al, 2009) with oligonucleotides GFPm F BamHI and GFPm R SalI (Table 2). Then the ompC promoter was amplified by PCR using OmpC F EcoRI and OmpC R SalI ( Table 2).…”
Section: Tablementioning
confidence: 99%